Pemahaman Undang-Undang Perkawinan terhadap Penundaan Perkawinan Usia Dini di Indonesia - Agoes Dariyo; Mia Hadiati; R. Rahaditya (Journal An-Nafs: Kajian Penelitian Psikologi, 2020)
Early age marriages have become widely reported through various media both print and electronic media, because early marriage is one of the causes of divorce in Indonesia. Divorce due to early marriage raises social problems in the community, such as high dropout rates for students, poverty, crime. The emergence of early marriage is caused by the low awareness of adolescents to understand Law number 1 of 1974 concerning marriage. This study discusses the understanding of law number 1 of 1974 concerning marriages which plays a role for adolescents to postpone early marriage in Indonesia. This research method uses a quantitative approach, involving 213 adolescent subjects with an age range of 17-22 years. Retrieval of data using a questionnaire that is the attitude of understanding marriage law, life satisfaction, resilience, and delaying early marriage. Analysis of research data using Spearman RHO correlation and non-linear regression. The results showed that the attitude of understanding marital law plays a role in delaying early marriage in adolescents in Indonesia.